Efek Kapsul Ekstrak Etanol Kulit Buah Delima (Punica granatum L.) terhadap Penanda Pembentukan dan Kualitas Tulang pada Wanita Pascamenopause - Handayani, Nur Hayati Dwi; Bahtiar, Anton; Louisa, Melva (Jurnal Kefarmasian Indonesia, 2017)
Studies of pomegranate peel (Punica granatum L.), which contain ellagic acid, suggest its ability to increase osteoblast, calcium, and phosphorus in ovariectomized rats. The effects of the pomegranate peel extracts on postmenopausal women was not known. This study was aimed to evaluate the effect of pomegranate peel ethanol extract capsules in the modulation of bone formation and bone quality markers in postmenopausal women. This study is a pilot study of 1st phase of clinical trial using parallel, randomized, double-blind, and placebo controlled design, with 30 subjects. Subjects were randomized to receive commercial capsules of pomegranate peel ethanol extract 2 × 1100 mg/ day or placebo, for 8 weeks. Levels of osteocalcin, calcium, and phosphorus were examined before and after treatment. This study showed that administration of the capsules in postmenopausal women tends to reduce blood osteocalcin level (4,129±5,66 ng/mL on placebo group versus 1,79±5,04 ng/mL on punica group, p=0,245), has not significant on blood calcium level (9,13±0,36 mg/dL placebo group versus 9,21±0,39 mg/dL punica group, p=0,379), has not significant on blood phosphorus level (3,93±0,38 mg/dL placebo group versus 4,12±0,41 mg/dL on punica group, p=0,138), does not affect the function of liver and kidney, and was well tolerated. In conclusion, the commercial capsules is safe, potentially reduce marker of bone formation serum level,and increase bone quality on postmenopausal women.